Respuesta :

Step-by-step explanation:

7x + 2 = 4x + 0

both sides substracted by 2

7x = 4x -2

both sides substracted by 4x

7x-4x = -2

3x = -2

both sides divided by 3

3x/3 = -2/3

=> x = -⅔

[tex]\\ \sf\bull\dashrightarrow 7x+2=4x+0[/tex]

  • Any no added with 0 will the number itself.Hence omit zero

[tex]\\ \sf\bull\dashrightarrow 7x+2=4x[/tex]

[tex]\\ \sf\bull\dashrightarrow 7x-4x=-2[/tex]

[tex]\\ \sf\bull\dashrightarrow 3x=-2[/tex]

[tex]\\ \sf\bull\dashrightarrow x=\dfrac{-2}{3}[/tex]